Kesesuaian Lahan Permukiman di Wilayah Pesisir Kecamatan Galesong Utara, Kabupaten Takalar - Ananda Lola Syam; Shirly Wunas; Wiwik Wahidah Osman (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2018)
Rapid population growth can cause problems related to the availability of land for settlements. Demand of the population which is greatly increased tends to ignore the designation and capability of existing land. Land use for settlements is regulated in regional spatial plans, taking into account the balance of physical and ecological aspects. The purpose of this study is to determine the suitability level of settlement land and formulate the principles of settlement development. Data collection methods used are, observation, questionnaire and literature study. The analytical method used is Analytical Hierarchy Process (AHP), spatial analysis, and descriptive analysis. Land suitability is seen through several aspects, namely slope, soil type, beach border, abrasion prone, fishing facilities, availability of clean water, accessibility, river border and land availability. The results of this study indicate that land is 110 Ha, which is 939 Ha, and 493 Ha. The suitability of the land to the appropriate category means that this land is suitable to be developed as a residential area with a high score for all aspects. The appropriate land classification is vacant land and shrubs. Land suitability with the category is quite appropriate, it means that special consideration is needed in the development of settlements. While the land suitability with the category does not match, it means that the development of residential areas can be carried out with a touch of technology, however, it must still be prioritized as a protected area. Most of the land with inappropriate categories is coastal border, river border and abrasion prone areas.